INVISIBLE ACTORS IN THE GREEK THEATRE: STAGING THE PROLOGUE OF SOPHOCLES’ AJAX - Maggel, Avgi-Anna (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
In the prologue of Sophocles' tragedy Ajax, three actors appear, playing the roles of Odysseus, Athena, and Ajax. The scene presents a particular dramatic interest because Sophocles devises a directorial device by making Athena invisible to Odysseus and, subsequently, Odysseus invisible to Ajax's eyes. The three actors interact in pairs of dialogues: first, between the supposedly invisible Athena and Odysseus, and then between Athena and Ajax, with Odysseus watching as a silent and unseen listener to the conversation of the two characters on stage. The aim of the present study is, firstly, to contribute to the discussion on the staging of the invisible Athena in the play's prologue, which raises the theatrical issue concerning her appearance on the theologeion (the roof or raised platform for gods), and secondly, to investigate the staging of the invisible Odysseus, which is combined with the silence he must observe at Athena's prompting to avoid being perceived by the raging Ajax. Conversely, the spectators watch the actors playing invisible characters in their encounters and are called upon to focus their attention on the text’s indications to understand the innovations in Sophocles' stage version of the myth of Ajax, which they know from the Homeric tradition.